2011
DOI: 10.1177/00333549111260s104
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Homes University: A Home-Based Environmental Intervention and Education Program for Families with Pediatric Asthma in Michigan

Abstract: Environmental conditions within the home can exacerbate asthmatic children's symptoms. To improve health outcomes among this group, we implemented an in-home environmental public health program-Healthy Homes Universityfor low-income families in Lansing, Michigan, from 2005 to 2008. Families received four visits during a six-month intervention. Program staff assessed homes for asthma triggers and subsequently provided products and services to reduce exposures to cockroaches, dust mites, mold, tobacco smoke, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…A small intervention study randomised a total of 160 HDM-sensitised children with asthma to either chemical, physical or both interventions or control and reported that children in the three intervention arms all had improvements of 2% predicted FEV 1 compared with control 28. A final intervention study, where there was no control arm and which was given a weak global rating and all 243 individuals were given a comprehensive allergen and educational intervention, found improved symptoms 6 months after intervention compared with baseline 29. One cohort study related grass pollen exposures to symptoms and rescue medication use in 430 children with asthma and reported associations among the subgroup of children in receipt of maintenance treatment and sensitised to grass 30.…”
Section: Resultsmentioning
confidence: 99%
“…A small intervention study randomised a total of 160 HDM-sensitised children with asthma to either chemical, physical or both interventions or control and reported that children in the three intervention arms all had improvements of 2% predicted FEV 1 compared with control 28. A final intervention study, where there was no control arm and which was given a weak global rating and all 243 individuals were given a comprehensive allergen and educational intervention, found improved symptoms 6 months after intervention compared with baseline 29. One cohort study related grass pollen exposures to symptoms and rescue medication use in 430 children with asthma and reported associations among the subgroup of children in receipt of maintenance treatment and sensitised to grass 30.…”
Section: Resultsmentioning
confidence: 99%
“…Seventy-five full-text articles were read. Forty-five studies were excluded for the following reasons: no relevant outcomes, 18 studies [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] ; the trial did not include a control group, 7 studies [56][57][58][59][60][61][62] ; the interventions were not aimed at parents of young children, 3 studies [63][64][65] ; the reporting period was ,1 month, 2 studies 66,67 ; data necessary for analysis were missing, 10 studies [68][69][70][71][72][73][74][75][76][77] ; the paper was a review article, 1 study 78 ; the article was a protocol, 2 studies 79,80 ; the article was a follow-up of a previous study, 1 study 81 ; there was no true control group (eg, 2 active interventions were compared), 1 study 82 .…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Previous studies showed that caregiver knowledge of asthma and asthma treatment could improve asthma control and severity in children. 12 Therefore, caregivers were strongly encouraged (though not required) to attend the camps and participate in the educational activities with their children so they could reinforce key concepts at home and increase their own asthma knowledge. The camp setting provided adequate space for large groups of children and caregivers to receive formal education.…”
Section: Designmentioning
confidence: 99%